2011
DOI: 10.1039/c1rp90024b
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness for tertiary chemistry: multiple applications of the Chemistry Competence Test for diagnostic and prediction purposes

Abstract: The development of the Chemistry Competence Test was prompted by the extensive curriculum changes in the South African school system after democracy was established in 1994. As chemists, we were concerned that there might be a lack of articulation between secondary and tertiary levels, since we anticipated that curriculum changes would have an impact on the knowledge base and skills development of prospective students. A diagnostic test developed initially to document proficiencies of first-time entering stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
0
18
0
1
Order By: Relevance
“…An in-depth study of a group of students at a specific Swedish upper secondary school understanding of matter and phase changes was published recently (Taber and Adbo, 2013). While some data has been collected about South African secondary students level of preparedness for tertiary studies (Potgieter and Davidowitz, 2011), there has been no in depth investigation of their ideas on chemical bonding. From these perspectives it would be especially fruitful for Swedish and South African chemistry teachers and researchers to obtain data regarding the frameworks of bonding held by their students.…”
Section: The Swedish -South African Chemical Bonding Studymentioning
confidence: 99%
“…An in-depth study of a group of students at a specific Swedish upper secondary school understanding of matter and phase changes was published recently (Taber and Adbo, 2013). While some data has been collected about South African secondary students level of preparedness for tertiary studies (Potgieter and Davidowitz, 2011), there has been no in depth investigation of their ideas on chemical bonding. From these perspectives it would be especially fruitful for Swedish and South African chemistry teachers and researchers to obtain data regarding the frameworks of bonding held by their students.…”
Section: The Swedish -South African Chemical Bonding Studymentioning
confidence: 99%
“…The quantitative approach was used. It was used because the instructor needed to ascertain and confirm what and how the assessment process is carried out so that it required a quantitative and in-depth interpretation of the research conducted (Potgieter & Davidowitz, 2011). The selected samples are 200 students of chemistry education department from semester 1 to semester 5.…”
Section: Methodsmentioning
confidence: 99%
“…Learning assessment is an important point that must be conducted by the teacher (Potgieter & Davidowitz, 2011). The assessment of learning provided contains a lot of essential information such as evaluating student learning progress, the extent of students' cognitive depth on learning that has been passed, and the accuracy of test instruments in measuring their mental models (Potgieter &. Davidowitz, 2011;Brannon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding conceptual difficulties, the most documented obstacles in teaching and learning about redox reactions among the selected articles is related to understanding the electron transfer process. Acar and Tarhan (2007), Loh and Subramaniam (2018), Potgieter and Davidowitz (2011) and Rahayu et al (2011) reported cases where students believe that electrons can flow through aqueous solutions. Brandriet and Bretz (2014) stated that, although students are able to identify where electrons are transferred to, they cannot describe the particulate process underlying the symbolic equation.…”
Section: Limitations Of Teaching and Learning Redox Reactionsmentioning
confidence: 99%